The Effect of The Biochar Application of Oil Palm Shells and Municipal Waste Compost on Soil Water Content of Coal Mine Reclamation and Soybean Yield - Endriani; Oktavia, Tika; Wiskandar (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2023)
Characteristics of the most prominent former coal mining land are severe damaged land, causing decreased soil productivity, erosion and sedimentation, soil movement and resulting in land slides, and soil compaction so that it is difficult to process. Efforts to improve the physical properties of coal mining reclamation soils, namely by adding biochar and compost. Biochar and compost can improve the physical properties of the soil by increasing the content of organic matter, total pore space, water content and reducing the weight of soil volume. This study uses a complete random design with 6 treatments and 4 replications. The treatment used in this study is B0 without treatment (control); B1 15 tons/ha biochar oil palm shells; B2 10 tons/ha biochar oil palm shells and 5 tons/ha of city waste compost; B3 7.5 tons/ha biochar oil palm shells and 7.5 tons/ha of city waste compost; B4 5 tons/ha Biochar palm oil shell and 10 tons/ha of city waste compost; B5 15 tons/ha of city waste compost. The observed variables are the content of organic matter, the weight of soil volume, total pore space, soil water content in several PF values, plant height, plant yields and the number of plant pods. The results obtained that the treatment combination of 7.5 tons/ha of biochar oil palm shells 7.5 tons/ha of city waste compost is the best composition to improve the groundwater content of coal mining reclamation. Furthermore, the provision of 15 tons/ha of city waste compost has effectively improved soybean yield. Keywords : biochar, compost, some physical properties, coal, soybeans